1998
DOI: 10.1016/s0893-133x(98)00043-8
|View full text |Cite
|
Sign up to set email alerts
|

Selective Effects of the Endogenous Cannabinoid Arachidonylethanolamide (Anandamide) on Regional Cerebral Blood Flow in the Rat

Abstract: The behavioral profile seen in humans following administration of marijuana has long been a source of intense interest, because the unique syndrome produced does not resemble that seen after any other psychoactive substance. Subjectively, the cannabinoid syndrome in humans includes sensory enhancement, errors in the judgment of time and space, dissociation of ideas, delusions, impulsivity, and hallucinations (Pertwee 1988). For example, individuals often report that while under the influence of cannabis, audit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 58 publications
4
26
0
Order By: Relevance
“…14 C]iodoantipyrene Imaging cocaine sensitization in awake rats M Febo et al autoradiography have shown cocaine-induced elevations in regions cerebral blood flow (Stein and Fuller, 1992). Increased flow of oxygenated blood to regions of enhanced neuronal activity and metabolism likely contributes to alterations in BOLD observed in this study and Febo et al (2004).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…14 C]iodoantipyrene Imaging cocaine sensitization in awake rats M Febo et al autoradiography have shown cocaine-induced elevations in regions cerebral blood flow (Stein and Fuller, 1992). Increased flow of oxygenated blood to regions of enhanced neuronal activity and metabolism likely contributes to alterations in BOLD observed in this study and Febo et al (2004).…”
Section: Discussionmentioning
confidence: 58%
“…Increased oxygenation of these areas contributes to the elevations in BOLD signal intensity (Thompson et al, 2003). An acute cocaine injection increases cerebral metabolic activity (Porrino, 1993) and blood flow (Stein and Fuller, 1992); effects that are likely to contribute to changes in BOLD signal intensity (Febo et al, 2004). These alterations could possibly involve effects of cocaine on synaptic monoamine levels throughout cortical and subcortical structures (Goeders and Smith, 1983;Kalivas and Duffy, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the effects of AEA on calcium and potassium channels would appear to be limited, since the major physiologic change produced by these actions, vasorelaxation and a decrease in systemic vascular resistance (Garcia et al 2001), require doses significantly higher than those used to block APO-induced stereotypy. Similarly, large changes in calcium and potassium conductance in basal ganglia neurons or local cerebral blood vessels might be expected to cause marked effects on cerebral blood flow or basal ganglia function: effects that are not observed at the highest dose used in this study (Stein et al 1998; present data). Thus, although there is evidence for interactions among AEA, calcium, and potassium chan- and biting (b), licking (c), and sniffing (d) stereotypies.…”
Section: The Specificity Of the Effects Of Carb And Aea On Electrotonmentioning
confidence: 54%
“…Limbic activation has indeed been demonstrated in four animal studies (58)(59)(60)(61) and in a recent human study using functional MRI (62). Cocaine's rapid temporal dynamics (63) and/or local vasoconstrictive actions may have prevented a demonstration of limbic effects in several other studies (64-69).…”
Section: Discussionmentioning
confidence: 85%